Fee Payment System for Nursing Performance: An operational proposal through the use of I.C.A. (Indexes of Complexity of Assistance) methodology - Schenone, Daniela; Rasero, Laura; Cavaliere, Bruno (Acta Biomedica Atenei Parmensis, 2018)
Background and Aim of the Study: The objective of this study is to demonstrate the feasibility of a possible fee system based on the performance of the nursing function, validating the theoretical and methodological assumption of an economic analysis for nursing. Method: The I.C.A. Methodology (Indexes of Complexity of Assistance) was chosen as a system able to produce the reading, in an economic sense, of nursing performance to a sufficiently accurate degree, by its use of “assistance settings” and “nursing assistance plans”. For the planning of assistance, the Nursing Interventions Classification (NIC) was used, as it is a validated and shared language. For the cost of each single operation/intervention and recovery, the “weight intervention” algorithm of the I.C.A. methodology was used. This research project was carried out in the form of a pilot study which investigated a sample of 30 patients, and a multi-center cross-sectional and observational retrospective study conducted on a sample of 135 patients coming from three Region of Liguria Hospitals.   Results: The study was concerned with 165 cases. It highlighted 65 D.R.G.s, of which 17 were selected, containing comprehensively 61 cases. The results obtained confirm that it is possible to use this proposed approach to calculate the direct and indirect costs of nursing activity, and that it is also possible to compare it to the present D.R.G. system. Conclusions: It is necessary to create a multidisciplinary payment system for a patient’s care. This must be able to monitor the whole treatment process, and therefore all of the activities carried out for the patient’s benefit. The present D.R.G. system is not able to register the care provided by nursing services.